Sport i politika: Sotsiologicheskij analiz vzaimodeistviya v stranakh SNG - Oleynik, N.; Ashanin, V.; Kamayev, O.; Kudinenko, V.; Taran, L.; Epstein, L. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
Sports as the major public phenomenon of XX th century, contrary to the idealistic formula of P. Coubertine can not insulate itself from socio economic and political processes. The specificity of the transitive period is in the sharp struggle for the governance in the countries of the CIS force strongly to base on athletes. For the confirmation of this hypothesis the authors have carried out the expert interrogation. 60 experts were involved in the research. The authors have offered to state the vision of the problem "sports and policy", answering on 6 main and number of additional questions. The absolute majority were unanimous: the getting stronger union of policy and sports is an objective phenomenon. Dangers of use of sports as utility of "dirty policy" experts realize already today. The main conclusion: the dialectics of policy and sports represents not only academic, but also the practical interest for modern political process of the countries of the CIS. Thus special urgency is got by study of: - mechanisms of the strengthening of the political representation of sports in the agencies of the state governance, lawful lobbying of its interests; - the effective use of all system of mass-media for propaganda support both the expansion of the representation of athletes and sports figures in legislative and executive agencies of governance.